2020
DOI: 10.1055/s-0040-1701698
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Free Flap Breast Protocol Optimizing Resources and Patient Safety

Abstract: Background As deep inferior epigastric artery perforator (DIEP) flaps have gained popularity in breast reconstruction, the postoperative care of these patients, including the appropriate hospital length-of-stay and the need for intensive care unit (ICU) admission, has become a topic of debate. At our institution, we have adopted a pathway that aims for discharge on postoperative day 3, utilizing continuous tissue oximetry without ICU admission. This study aims to evaluate outcomes with this pathway to assess i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…17,18 However, overall health care savings have been demonstrated when the tissue oximetry use permits for flap monitoring on the ward rather than the ICU. 3,5,14 Our findings show false positive alarms as an additional disadvantage of transcutaneous tissue oximetry monitoring. Causes of erroneous readings include poor signal quality due to overhead operating room lights, initial probe position directly over a vessel that will give saturation readings that are not representative of flap perfusion, and a falsely elevated initial reading while the patient is still intubated and under general anesthesia.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…17,18 However, overall health care savings have been demonstrated when the tissue oximetry use permits for flap monitoring on the ward rather than the ICU. 3,5,14 Our findings show false positive alarms as an additional disadvantage of transcutaneous tissue oximetry monitoring. Causes of erroneous readings include poor signal quality due to overhead operating room lights, initial probe position directly over a vessel that will give saturation readings that are not representative of flap perfusion, and a falsely elevated initial reading while the patient is still intubated and under general anesthesia.…”
Section: Discussionmentioning
confidence: 68%
“…3 Other investigators have shown benefits of incorporating tissue oximetry in flap monitoring protocols as well. [14][15][16] Although the literature demonstrates benefits of transcutaneous tissue oximetry monitoring, the primary disadvantage is cost. The disposable sensor probes average $1,000 each with consoles costing about $30,000.…”
Section: Discussionmentioning
confidence: 99%
“…ERAS protocols have demonstrated ability to standardize postoperative stays and facilitate discharge. [12][13][14][15][16][17] Our study has exhibited the influence of patient expectation of discharge. We have shown that setting an expectation of a particular early discharge date can significantly affect the LOS.…”
Section: Discussionmentioning
confidence: 86%
“…The implementation of enhanced recovery after surgery (ERAS) protocols has improved postoperative pain, minimized narcotics, and reduced LOS without increasing postoperative adverse effects. [12][13][14][15][16][17] The literature also shows that transversus abdominis plane (TAP) blocks reduce the level of narcotics that patients require to control their pain after abdominally based breast reconstruction. 18,19 Goals of DIEP flap postoperative protocols include enhanced patient outcomes, improved pain control with minimizing narcotics, and controlling costs with decreasing LOS.…”
mentioning
confidence: 99%
“…2,3 They concluded that bypassing the ICU and opting for immediate floor level care with continuous tissue oximetry achieves reduced hospital cost, improved access to ICU beds, and has an acceptable rate of flap failure. 21 Similarly, in a study by Carruthers et al, no patients were admitted to the ICU postoperatively. Instead, they underwent hourly flap checks for the first 12 hours, transitioning to every 4 hours after that, with continuous tissue oximetry until discharge.…”
Section: Discussionmentioning
confidence: 95%